PENGARUH MEDIA PEMBELAJARAN FILM KARTUN TERHADAP KEMAMPUAN BERBICARA DALAM MENCERITAKAN KEGEMARAN SISWA DI KELAS II SDN 1 SUKAMULYA - Ajeng Sinta Wati; Dessy Wardiah; Aldora Pratama (STKIP Subang, 2023)
The Influence Of Cartoon Learning Media To Improve The Ability To Tell Student' Hobbie In Grade II SDN 1 Sukamulya. The purpose of this study was to determine the influence of cartoon ffilm media to improve speaking skills in telling students' hobbies in grade II SDN 1 Sukamulya. This research uses the One Group Pretest Design method – Posstest Design. The unit of analysis in this study is the cartoon film